Investigating English Vocabulary Mastery and Its Influencing Factors in a Multilingual Islamic School: Evidence from Southern Thailand - Dina Auliya; Wandi Syahfutra; Qonaah Nuryan Arif (Yayasan Pendidikan Bima Berilmu, 2026)
This study investigates English vocabulary mastery and the factors influencing it among students in a multilingual Islamic school in Southern Thailand. The study employed a descriptive quantitative method with a cross-sectional survey design involving 31 seventh grade students at Jareeyatam Islamic Foundation School. Data were collected through a 25 items vocabulary test and a 20 items questionnaire measuring English exposure, English use, multilingual interference, and learning motivation. The data were analyzed using descriptive statistics, including frequencies, percentages, and mean scores. The findings revealed that students’ vocabulary mastery was generally very low, with a mean score of 42.97. Most participants (67.74%) were categorized at the very low level of vocabulary mastery. Among the factors examined, English exposure (M = 2.90) and learning motivation (M = 2.61) were at a moderate level, whereas English use (M = 2.40) and multilingual interference (M = 2.31) were at a low level. The results suggest that limited active use of English was the primary factor contributing to students’ low vocabulary mastery. Although students demonstrated moderate exposure to English and learning motivation, insufficient opportunities to practice English meaningfully hindered vocabulary development. Therefore, increasing communicative and interactive English learning activities may help improve vocabulary acquisition in multilingual educational settings.